Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure! Let's solve the equation step by step:
We start with the given equation:
[tex]\[ 4x - 8 = -4(2x - 3) + 4 \][/tex]
1. Distribute the [tex]\(-4\)[/tex] on the right side of the equation:
[tex]\[ -4(2x - 3) = -4 \cdot 2x + (-4 \cdot -3) \][/tex]
[tex]\[ -4(2x - 3) = -8x + 12 \][/tex]
2. Substitute [tex]\(-8x + 12\)[/tex] back into our equation:
[tex]\[ 4x - 8 = -8x + 12 + 4 \][/tex]
3. Combine like terms on the right side:
[tex]\[ 4x - 8 = -8x + 16 \][/tex]
4. Add [tex]\(8x\)[/tex] to both sides to start isolating [tex]\(x\)[/tex]:
[tex]\[ 4x + 8x - 8 = 16 \][/tex]
[tex]\[ 12x - 8 = 16 \][/tex]
5. Add [tex]\(8\)[/tex] to both sides to further isolate [tex]\(x\)[/tex]:
[tex]\[ 12x - 8 + 8 = 16 + 8 \][/tex]
[tex]\[ 12x = 24 \][/tex]
6. Finally, divide both sides by [tex]\(12\)[/tex] to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{24}{12} \][/tex]
[tex]\[ x = 2 \][/tex]
The solution to the equation [tex]\( 4x - 8 = -4(2x - 3) + 4 \)[/tex] is [tex]\( x = 2 \)[/tex].
We start with the given equation:
[tex]\[ 4x - 8 = -4(2x - 3) + 4 \][/tex]
1. Distribute the [tex]\(-4\)[/tex] on the right side of the equation:
[tex]\[ -4(2x - 3) = -4 \cdot 2x + (-4 \cdot -3) \][/tex]
[tex]\[ -4(2x - 3) = -8x + 12 \][/tex]
2. Substitute [tex]\(-8x + 12\)[/tex] back into our equation:
[tex]\[ 4x - 8 = -8x + 12 + 4 \][/tex]
3. Combine like terms on the right side:
[tex]\[ 4x - 8 = -8x + 16 \][/tex]
4. Add [tex]\(8x\)[/tex] to both sides to start isolating [tex]\(x\)[/tex]:
[tex]\[ 4x + 8x - 8 = 16 \][/tex]
[tex]\[ 12x - 8 = 16 \][/tex]
5. Add [tex]\(8\)[/tex] to both sides to further isolate [tex]\(x\)[/tex]:
[tex]\[ 12x - 8 + 8 = 16 + 8 \][/tex]
[tex]\[ 12x = 24 \][/tex]
6. Finally, divide both sides by [tex]\(12\)[/tex] to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{24}{12} \][/tex]
[tex]\[ x = 2 \][/tex]
The solution to the equation [tex]\( 4x - 8 = -4(2x - 3) + 4 \)[/tex] is [tex]\( x = 2 \)[/tex].
Answer:
x=2
Step-by-step explanation:
4x - 8 = -4(2x - 3) + 4
Distribute the -4.
4x-8 = -8x+12 +4
Combine like terms.
4x-8 = -8x+16
Add 8x to each side.
4x+8x-8 = -8x+8x-16
12x-8 = 16
Add 8 to each side.
12x-8+8 = 16+8
12x = 24
Divide each side by 12.
12x/12 = 24/12
x=2
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.